2023
DOI: 10.1186/s13071-023-05711-6
|View full text |Cite|
|
Sign up to set email alerts
|

The sex pheromone heptacosane enhances the mating competitiveness of sterile Aedes aegypti males

Abstract: Background Aedes aegypti is a vector that transmits various viral diseases, including dengue and Zika. The radiation-based sterile insect technique (SIT) has a limited effect on mosquito control because of the difficulty in irradiating males without reducing their mating competitiveness. In this study, the insect sex pheromone heptacosane was applied to Ae. aegypti males to investigate whether it could enhance the mating competitiveness of irradiated males. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Even though many individual compounds are shared between species, we found chemical blends to be highly species-specific, a feature that may be indicative of evolution primarily for mate recognition (Gomez-Diaz & Benton, 2013; Symonds & Elgar, 2008; Wyatt, 2014). This is further supported by the fact that many of the shared compounds detected in this study function as pheromones in other insects (Yang et al ., 2017; Funaro et al ., 2018; Wang et al ., 2023). This includes octadecanal, which is used by H. melpomene in female mate choice (Byers et al, 2020), and is found in varying concentrations across four Heliconiini and three Ithomiini species.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many individual compounds are shared between species, we found chemical blends to be highly species-specific, a feature that may be indicative of evolution primarily for mate recognition (Gomez-Diaz & Benton, 2013; Symonds & Elgar, 2008; Wyatt, 2014). This is further supported by the fact that many of the shared compounds detected in this study function as pheromones in other insects (Yang et al ., 2017; Funaro et al ., 2018; Wang et al ., 2023). This includes octadecanal, which is used by H. melpomene in female mate choice (Byers et al, 2020), and is found in varying concentrations across four Heliconiini and three Ithomiini species.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Anopheles spp. have been shown to mate in swarms of flying males, often consisting of a few to many thousands of mosquitoes (Oliva et al, 2014;Wang et al, 2021Wang et al, , 2023.…”
Section: Matingmentioning
confidence: 99%
“…Mosquitoes use both auditory (Feugere et al, 2021(Feugere et al, , 2022 and may or may not use chemical cues to attract both sexes to mate in a swarm (Fawaz et al, 2014;Mozuraitis et al, 2020;Poda et al, 2022;Wang et al, 2021Wang et al, , 2023. Both sexes are sensitive to auditory cues and swarm in the air to mate (Feugere et al, 2021;Su et al, 2018).…”
Section: Matingmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], two errors came to the attention of the authors: Mao Zhang had not been indicated as a co-first author, and in the Funding declaration, the funding number of the National Natural Science Foundation of China had been incorrectly detailed as ‘8210082025’ instead of ‘82102432’, the correct number.…”
mentioning
confidence: 99%